PENERAPAN MODEL PEMBELAJARAN BERBASIS PROJEK (PBL) PADA MATA KULIAH PRAKTIK INDUSTRI - Sukatiman, Sukatiman (Jurnal Inovasi Pendidikan, 2009)
A Project Based Learning (PBL) is a method in modern learning using different concepts from the conventional learning. PBL concepts are emphasized on cycles of learning process. They consist of planning, action, field observation, evaluation, and reflection. PBL needs the participation of teacher to be facilitator, advisor, and as colleagues not to be an expert. PBL will ensure the student active in learning, increase student's motivation, give the solution about the problem, and finish the field problems according to the competence of the student with certain progress. The advantage of teaching learning process using PBL is increasing student?s knowledge in industry.